Perlindungan Hukum terhadap Pengguna Jasa Angkutan Umum pada Dinas Perhubungan Kota Medan - Zainal Fikri Nasution; Isnaini Isnaini; Sri Hidayani (Universitas Medan Area, 2017)
Legal Protection on The Users of Public Transport Services in Medan City Transportation OfficeAbstractLegal protection is any effort that guarantees legal certainty to provide protection to passengers or consumers who use the services of business people to protect them from things they do not want. Public Transportation is one of the transportation media used by the community together by paying tariffs. The purpose of this study was to determine the legal standing of public transport passengers and their protection in accordance with Law No.22 of 2009 concerning Road Traffic and transportation. The type of writing in this study is Normative, namely a process to find a rule of law, legal principles, and legal doctrines in order to answer the legal issues at hand. Public Transport Companies are responsible for losses caused by all actions of people employed in the activities of transport operations. In addition, the Public Transport Company is responsible for losses suffered by Passengers who have died or injuries due to transportation operations, unless caused by an incident that cannot be prevented due to passenger error.